Dosimetric benefit to organs at risk following margin reductions in nasopharyngeal carcinoma treated with intensity‐modulated radiation therapy. Issue 3 (20th May 2015) - Mao, Yan‐Ping; Yin, Wen‐Jing; Guo, Rui; Zhang, Guang‐Shun; Fang, Jian‐Lan; Chi, Feng; Qi, Zhen‐Yu; Liu, Meng‐Zhong; Ma, Jun; Sun, Ying
Abstract: Introduction: It is important to decrease the radiation exposure of normal tissue in intensity‐modulated radiation therapy (IMRT). Minimizing planning target volume (PTV) margins with more precise target localization techniques can achieve this goal. This study aimed to quantify the extent to which organs at risk (OARs) are spared when using reduced margins in the treatment of nasopharyngeal carcinoma (NPC). Methods: Two IMRT plans were regenerated for 40 patients with NPC based on two PTV margins, which were reduced or unchanged following cone beam computed tomography online correction. The reduced‐margin plan was optimized based on maximal dose reduction to OARs without compromising target coverage. Dosimetric comparisons were evaluated in terms of target coverage and OAR sparing. Results: Improvements in target coverage occurred with margin reduction, and significant improvements in dosimetric parameters were observed for all OARs ( P < 0.05) except for the right optic nerve, chiasm, and lens. Doses to OARs decreased at a rate of 1.5% to 7.7%. Sparing of the left parotid and right parotid, where the mean dose (Dmean ) decreased at a rate of 7.1% and 7.7%, respectively, was greater than the sparing of other OARs. Conclusions: Significant improvements in OAR sparing were observed with margin reduction, in addition to improvement in target coverage. The parotids benefited most from the online imaging‐guided approach.